Pemberian informasi melalui SMS terhadap sikap seks pranikah remaja SMA - Yayuk Puji Rahayu; Sabar Santoso; Yuliasti Eka Purnamaningrum (Jurnal Kesehatan Ibu dan Anak, 2016)
The percentage of adolescent premarital sexual intercourse increases every year. SMS is one of the important medias forhealth promotion including adolescent health reproduction such as premarital sexual intercourse. This research was aimed to determine the effect of giving information through SMS on the increase of the adolescent attitude on the premarital sexual intercourse of the senior high school students. This research was categorized into quasi-experimental research which hada pre-posttest with a control group design conducted on 35 respondents both the experimental group and the control group. Thisresearch was conducted at SMAN 1 Pundong as the experiment group given intervention through SMS and SMAN 1 Kretekas the control group was given intervention through leaflets. The instrument used was questionnaire. The data analysis used was thestatistic parametric with significance-0,05. The result of pretest showed that the average score of the experiment group was124,1 while the control group's average score was 119,97. The result of the posttest showed that the average score of the experimentgroup was 131,6 while the control group's average score was 119,90. Thus, it could beconcluded that there was a significantdifference between pretest and posttest. The attitude of the experiment group increased up to 7,54 while the control group'sattitude increased only up to 0,23. The result gap of the two groups was 7,77. The result of the independent sample t-testwas thescoreof p-value 0,0004816 and 95% confidence interval was 3,5432-11,9997. The research concluded that there were someeffects of giving information through SMS on the increase of the attitude on premarital sex of X grade students of SMAN 1Pundong year 2014.